Dissociation between vasodilation and Leishmania infection-enhancing effects of sand fly saliva and maxadilan - Fábio Castro-Sousa; Moacir Paranhos-Silva; Ítalo Sherlock; Mariza S Paixão; Lain C Pontes-de-Carvalho; Washington LC dos-Santos (Memorias do Instituto Oswaldo Cruz, 2001)
In this study, the ability of maxadilan and Lutzomyia longipalpis salivary gland lysate to enhance the infection of CBA mice by Leishmania major and of BALB/c mice by L. braziliensis was tested. No difference was observed between sizes of lesion in CBA mice infected with L. major and treated or not with salivary gland lysate or maxadilan, although they were injected in concentrations that induced cutaneous vasodilation. Although parasites were more frequently observed in foot pads and spleens of animals treated with maxadilan than in the animals treated with salivary gland lysate or saline, the differences were small and not statistically significant. The lesions in BALB/c mice infected with L. braziliensis and treated with maxadilan were slightly larger than in animals that received Leishmania alone. Such differences disappeared 14 weeks after infection, and were statistically significant only in one of two experiments.